Controlling Droplet Evaporation in Aerosol Jet Printing to Understand and Mitigate Overspray - Bella I. Guyll; Brayden L. Sanford; Cary L. Pint; Ethan B. Secor (Small Science, 2025)
Aerosol jet printing is an additive manufacturing technique with broad materials compatibility, high resolution, and complex geometric capabilities. Despite these advantages, even optimized prints are susceptible to overspray, in which sparse deposition of material outside the primary pattern limits precision and quality for high‐value applications. Herein, a method is presented to overcome this by loading the sheath gas with solvent vapor before entering the printhead. This reduces droplet drying in the aerosol phase at the periphery of the aerosol stream, improving line edge morphology, pitch, porosity, and surface finish. This is demonstrated to reduce the overspray extent for a water‐based polyimide ink by up to 70 ± 2.3% and decrease the resistivity of a solvent‐based silver ink by 34 ± 13%. The ability to regulate droplet evaporation in flight offers versatile control, facilitating a wider range of process parameters and ink chemistries. These experimental results are backed by theoretical analysis and numerical modeling, providing a more refined and generalizable understanding of the underlying process physics. This enables tailored outcomes for a range of challenges including high aspect ratio and high‐density patterning with improved surface finish and material functionality for compelling applications in printed and hybrid electronics.